BANK HEALTH LEVEL ANALYSIS BEFORE, DURING, AND AFTER COVID-19 PANDEMIC - Widyawan, Albertus Prima Kristriyana; Lindrawati, Lindrawati (Kesatuan Press, 2025)
The COVID-19 pandemic has weakened the economy, causing third-party funds to grow, but credit interest has decreased, making banks face difficulties channeling funds to generate interest income. The implementation of social restrictions has led to many companies being unable to operate, which has slowed down the repayment of obligations by debtors, ultimately affecting banking health. This study aims to analyze differences in health levels of banks listed on the Indonesia Stock Exchange before, during, and after the COVID-19 pandemic. The research design is quantitative, using an event study to assess the impact of the COVID-19 pandemic. Bank health is measured using risk profile, good corporate governance (GCG), earnings, and capital. Data analysis was performed using the Wilcoxon signed-rank test. The results show differences in liquidity risk, operational risk, profitability, and capital during the periods before and during the pandemic, while there were no differences in credit risk, market risk, and GCG. During and after the pandemic, there were differences in credit risk, liquidity, operational risk, GCG, profitability, and capital, while market risk showed no difference. Before and after the pandemic, credit risk, liquidity, operational risk, and capital showed differences, while market risk, GCG, and profitability showed no differences.